Role of Water Resource Management in Achieving Sustainable Agriculture in Arid and Semi-Arid Zones (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Planned management of natural resources with the goal of maximizing their usefulness, efficient use in their original application, reuse, and recycling is known as resource conservation.  The goal is to reduce energy consumption and waste at every step, starting with manufacturing and continuing all the way to disposal.  Reduce your environmental footprint with the help of a resource conservation system that makes smart use of Earth's natural resources.  In dry regions, variability in soil, temperature, and socioeconomic elements is significant, making each place unique; hence, the appropriate selection of technology tailored to individual locales is essential.   In order to achieve this goal, there has to be a more effective management of natural resources in order to reduce the environmental impact of the goods throughout their entire lifecycle, from sourcing of raw materials to final disposal.  Predominantly agricultural systems can only achieve agricultural development that is ecologically sustainable if they guarantee in protecting, improving, and overseeing their water and land resources while simultaneously improving farmers' productivity, profitability, and prosperity.